2020
DOI: 10.1155/2020/6153234
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Patient Satisfaction and Associated Factors among Psychiatric Patients Who Attend Their Treatment at Outpatient Psychiatry Clinic, Jimma University Medical Center, Southwest Ethiopia, Jimma, 2019

Abstract: Background. In health care, patient satisfaction is an attitudinal response and a pillar for quality assurance, but there is reluctance to measure it among mentally ill patients. Satisfied patients become more compliant. However, no study was done in this study area before. Therefore, this study was conducted to determine the magnitude of perceived patient satisfaction and associated factor at Jimma University Medical Center, outpatient psychiatry clinic. Methods. Cross-sectional study design was conducted, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 30 publications
8
9
1
Order By: Relevance
“…It was also lower than the study done in Gondar (77%) 95% CI (0.70–0.84) [ 10 ] which might be explained by the difference in the setting of the service such as expert professionals, medication availability, Physical setup, and patient flow. This study found that 307 (75%) of respondents responded disagree, and strongly disagree with the item of referral to a specialist is possible, and this finding was contrary to the studies done in Jimma [ 9 ], 89% of them said agree and strongly agree to the item, and it might be due to lack of specialist and organized service on or nearby this study area.…”
Section: Discussioncontrasting
confidence: 90%
See 4 more Smart Citations
“…It was also lower than the study done in Gondar (77%) 95% CI (0.70–0.84) [ 10 ] which might be explained by the difference in the setting of the service such as expert professionals, medication availability, Physical setup, and patient flow. This study found that 307 (75%) of respondents responded disagree, and strongly disagree with the item of referral to a specialist is possible, and this finding was contrary to the studies done in Jimma [ 9 ], 89% of them said agree and strongly agree to the item, and it might be due to lack of specialist and organized service on or nearby this study area.…”
Section: Discussioncontrasting
confidence: 90%
“…This study found that waiting time was negatively associated with patient satisfaction (β = -2.19, 95% CI, (-5.238,-1.321, P = 0.001), and this study finding has supported the studies done by Mekelle [ 26 ] and Jimma [ 9 ]. The time they spend in the hospital without receiving care has an impact on their ability to return home and work, as well as on their caregivers.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations